Intramolecularly O,N,O‐coordinated tin(II) salts: syntheses, structures, cyclization, and transition metal complexation - Alnasr, Hazem; Mroß, David; Platzek, André; Nayyar, Bastian; Řičica, Tomáš; Schollmeyer, Dieter; Jambor, Roman; Hoffmann, Alexander; Jurkschat, Klaus (Wiley, 2024)
We report the syntheses of tin(II) salts of the types [L1SnX]SnX3 [L1=2,6-{(i-PrO)2(O)P}2C5H3N: 1, X=Cl; 2, X=Br], [L2SnCl]SnCl3 [L2=2-{(i-PrO)Ph(O)P}-6-{(i-PrO)2(O)P}C5H3N: 3], [L3SnX]SnX3 [L3=2,6-{MeO(O)C}2C5H3N: 4, X=Cl; 5, X=Br], [L4SnX]SnX3 [L4=2,6-{Et2N(O)C}2C5H3N: 6, X=Cl; 7, X=Br]. These compounds were obtained by addition of SnX2 to the corresponding ligand inducing autoionization of the respective tin(II) halide. The thermal stability of 1, 3, and 4 was elucidated, giving, under ester cleavage and cyclisation, the tin(II) derivatives 8–12. The reaction of [L1SnCl]SnCl3 (1) with W(CO)4(thf)2 afforded the tungsten tetracarbonyl complex [{L1SnCl}{SnCl3}W(CO)4] (13), representing the first example in which a tin(II) stannate anion and a tin(II) stannylium cation simultaneously coordinate to a transition metal centre. The compounds were characterized by single crystal X-ray diffraction analyses and in part by elemental analyses, IR and NMR spectroscopy, electrospray ionization mass spectrometry. DFT calculations accompany the experimental work.
Chemistry - a European journal; 30(45)
Keywords: Tin cation; X-ray diffraction; Tungsten tetracarbonyl complex; DFT calculations; Ester cleavage; 540